KEMAMPUAN ANTAGONIS Tricoderma harzianum TERHADAP BEBERAPA JAMUR PATOGEN PENYAKIT TANAMAN - Anton Muhibuddin; Syauqina Salsabila; Antok Wahyu Sektiono (AGROSAINTIFIKA, 2021)
Diseases that often attack plants are diseases caused by fungal pathogens causing stress such as fusarium wilt disease caused by Fusarium oxysporum, Alternaria solani, Rhizoctonia solani and Sclerotium rolfsii. One alternative to reduce these pathogens is Trichoderma harzianum. This study aims to determine the potential antibiosis antagonist characteristics of the fungus Trichoderma harzianum against several disease-causing pathogens in plants and the class of compounds contained therein.The method used in this research is experimental and descriptive. Experimental research was conducted by testing the fungus Trichoderma harzianum against several pathogenic fungi as an antibiosis. Then proceed to test the class of compounds using a phytochemical test on the filtrate of the secondary metabolites of Trichoderma harzianum. The results of the potential antibiosis antagonist test on the fungus Trichoderma harzianum showed the results of the antibiosis against the pathogenic fungi Fusarium oxysporum and the fungus Alternaria solani, but on the fungus Rhizoctonia solani and the fungus Sclerotium rolfsii, the results showed the presence of potential antibiosis followed by competition and parasitism. Inhibition on the seventh day of observation showed results of 79% against Fusarium oxysporum, 69% against Sclerotium rolfsii, 61% against Alternaria solani, and 59% against Rhizoctonia solani. Furthermore, for the phytochemical test, the filtrate of Trichoderma harzianum fungus showed positive content of alkaloids, flavonoids, steroids, and saponins.